Christelike etiek vanuit die perspektief van naasteliefde: Rudolf Bultmann en Stoïsynse etiek - Aarde, Andries van (HTS teologiese studies, 2015)
Christian ethics from the perspective of neighbourly love: Rudolf Bultmann and Stoic ethics. This article consists of various sections. The first concerns a cultural-sensitive explanation of the meaning of the term ‘neighbour’. The second exemplifies Rudolf Bultmann’s understanding of the meaning of the love commandment which is found in the Jesus tradition and in the New Testament. This explanation represents a paraphrase of Bultmann’s reflection on the notion ’neighbourly love’ in Afrikaans. The article elaborates on Bultmann’s interpretation by means of expanded exegetical comments. The article also endorses Bultmann’s juxtaposition of Christian ethics with Greek Stoic ethics. This Greek heritage is described in an expanded way. The article discusses Bultmann’s understanding of neighbourly love within the context of the core values of his hermeneutics. The results are made relevant for the present-day Christian ethical perspective on the adherence to the so-called natural law, applied to the South African sociopolitical situation.